Impact Testing of 3D Re-Entrant Honeycomb Polyamide Structure Using Split Hopkinson Pressure Bar - Jiangping Chen (MDPI AG, 2021)
In this study, a total of 30 3D re-entrant honeycomb specimens made of polyamide were fabricated with various configurations by using the additive manufacturing (AM) technique. Split Hopkinson Pressure Bar (SHPB) tests were conducted on the RH specimens at different impact velocities. The incident, reflected and transmitted waveforms can well explain the wave propagation and energy absorption characteristics of the specimens, which can help us to understand and analyse the process of impact loading. The stress–strain curves, energy absorption ability and failure modes of SHPB tests with different impact velocities and quasi-static compression tests were analysed and compared, and it was found that the flow stress and energy absorption ability of the specimens subjected to impact load were much improved. Among the tested specimens, specimen C2, with a smaller re-entrant angle θ, displayed the best energy absorption ability, which was 1.701 J/cm3 at the impact velocity of 22 m/s and was 5.1 times that in the quasi-static test. Specimen C5 had the longest horizontal length of the diagonal bar <semantics>L0</semantics>, and its energy absorption was 1.222 J/cm3 at the impact velocity of 22 m/s and was 15.7 times that in the quasi-static test, reflecting the superiority of a structurally stable specimen in energy absorption under impact loading. The test results can provide a reference for the optimization of the design of the same or similar structures.